Global Behavior of a Discrete Survival Model with Several Delays - Meirong Xu; Yuzhen Wang (Journal of Applied Mathematics)
The difference equation yn+1−yn=−αyn+∑j=1mβje−γjyn−kj is studied and some sufficient conditions which guarantee that all solutions of the equation are oscillatory, or that the positive equilibrium of the equation is globally asymptotically stable, are obtained.